New biomarkers and imaging approaches for the diagnosis of deep venous thrombosis. Issue 3 (May 2017) - Schaefer, Jordan K.; Jacobs, Benjamin; Wakefield, Thomas W.; Sood, Suman L.
Abstract : Purpose of review: Symptoms suggestive of deep vein thrombosis (DVT) are extremely common in clinical practice, but unfortunately nonspecific. In both ambulatory and inpatient settings, clinicians are often tasked with evaluating these concerns. Here, we review the most recent advances in biomarkers and imaging to diagnose lower extremity DVT. Recent findings: The modified Wells score remains the most supported clinical decision rule for risk stratifying patients. In uncomplicated patients, the D-dimer can be utilized with risk stratification to reasonably exclude lower extremity DVT in some patients. Although numerous biomarkers have been explored, soluble P-selectin has the most promise as a novel marker for DVT. Imaging will be required for many patients and ultrasound is the primary modality. Nuclear medicine techniques are under development, and computed tomography (CT) and magnetic resonance venography are reasonable alternatives in select patients. Summary: D-dimer is the only clinically applied biomarker for DVT diagnosis, with soluble P-selectin a promising novel biomarker. Recent studies have identified several other potential biomarkers. Ultrasound remains the imaging modality of choice, but CT, MRI, or nuclear medicine tests can be considered in select scenarios.